Associations between malaria in pregnancy and neonatal neurological outcomes. (November 2021) - Lawford, Harriet L.S.; Nuamah, Mercy A.; Liley, Helen G.; Griffin, Alison; Lekpor, Cecilia E.; Botchway, Felix; Oppong, Samuel A.; Samba, Ali; Badoe, Ebenezer V.; Kumar, Sailesh; Lee, Anne CC; Gyasi, Richard K.; et al.
Highlights: A prospective observational study of in utero malaria exposure and neonatal neurological functioning was conducted. In utero malaria exposure may increase the risk of suboptimal reflexes in term-born neonates. The impact of in utero malaria exposure on child neurodevelopment must be established. Abstract: Objective: To compare neurological functioning of neonates born to mothers with and without malaria in pregnancy. Methods: Pregnant women presenting at Korle Bu Teaching Hospital, Ghana were recruited into this prospective observational study. Malaria exposure was determined by clinically documented antenatal malaria infection; parasitemia in maternal, placental, or umbilical cord blood; or placental histology. Neurological functioning was assessed using the Hammersmith Neonatal Neurological Examination within 48 hours of birth. Performance was classified as "optimal" or "suboptimal" by subdomain and overall. Results: Between November 21, 2018 and February 10, 2019, a total of 211 term-born neonates, of whom 27 (13%) were exposed to malaria in pregnancy, were included. In the reflexes subdomain, exposed neonates tended to score lower (adjusted mean difference -0.34, 95% confidence interval -0.70 to 0.03), with an increased risk (adjusted risk ratio 1.63, 95% confidence interval 1.09 to 2.44) of suboptimal performance compared with unexposed neonates. There were no significant between-group differences in scores or optimality classification for the remaining subdomains and overall. Conclusions: Malaria-exposed neonates had similar neurological functioning relative to unexposed neonates, with differences confined to the reflexes subdomain, suggesting potential underlying neurological immaturity or injury. Further studies are needed to confirm these findings and determine the significance of malaria in pregnancy on long-term neurological outcomes.